2004
DOI: 10.1007/s00726-004-0072-x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous production of hydrogen sulfide in mammals

Abstract: Hydrogen sulfide is one of three gases involved in biological functions and synthesized in vivo. Like NO and CO, it seems to act as a neuromodulator: it modulates NMDA glutamate receptor function. CBS seems to be the only source of hydrogen sulfide in the brain, whereas the liver synthesizes hydrogen sulfide via cystathionase. In the heart, the third pathway for the hydrogen sulfide synthesis, the 3-mercaptopyruvate pathway is used. Only two diseases characterized by alterations of hydrogen sulfide metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
303
0
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(315 citation statements)
references
References 65 publications
3
303
0
9
Order By: Relevance
“…Recently, our group demonstrated that exogenous H 2 S promoted PLC/PRF/5 cell proliferation, anti-apoptosis, angiogenesis and migration by amplifying the activation of the NF-κB signaling pathway (24). To further investigate the effect of exogenous H 2 S on PLC/PRF/5 cells, PLC/PRF/5 cells were treated with 500 µmol/l NaHS for 24 h. The results revealed that exogenous H 2 S increased PLC/PRF/5 cell growth, angiogenesis and migration, as evidenced by an increase in cell viability, migration, expression of MMP-2 and production of VEGF, and a decrease in apoptotic rate and expression of caspase-3 (one of the apoptotic factors) (42), which is consistent with the findings of our previous study (23).…”
Section: The Stat3-cox-2 Signaling Pathway Participates In Nahs-inducsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, our group demonstrated that exogenous H 2 S promoted PLC/PRF/5 cell proliferation, anti-apoptosis, angiogenesis and migration by amplifying the activation of the NF-κB signaling pathway (24). To further investigate the effect of exogenous H 2 S on PLC/PRF/5 cells, PLC/PRF/5 cells were treated with 500 µmol/l NaHS for 24 h. The results revealed that exogenous H 2 S increased PLC/PRF/5 cell growth, angiogenesis and migration, as evidenced by an increase in cell viability, migration, expression of MMP-2 and production of VEGF, and a decrease in apoptotic rate and expression of caspase-3 (one of the apoptotic factors) (42), which is consistent with the findings of our previous study (23).…”
Section: The Stat3-cox-2 Signaling Pathway Participates In Nahs-inducsupporting
confidence: 89%
“…In the liver, H 2 S can be catalyzed by both cystathionine b-synthase (CBS) and cystathionine g-lyase (CSE) (23). Accumulating studies have demonstrated that H 2 S is involved in the pathophysiological progression of tumors (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological concentrations of H 2 S selectively enhance NMDA receptor-mediated responses and may modulate synaptic activities regulated by steroid hormones and neurotransmitters, suggesting that endogenous H 2 S functions as a neuromodulator in the brain (8). In the brain and the vasculature, micromolar quantities of H 2 S are produced by enzymes of the cysteine biosynthetic pathway (9,10). H 2 S is believed to act as a gaseous messenger like nitric oxide (NO) and carbon monoxide (CO).…”
mentioning
confidence: 99%
“…H 2 S production has been attributed to two key enzymes in the cysteine biosynthesis pathway, cystathionine ␤-synthase (CBS) and cystathionine ␥-lyase (CGL). CBS and CGL are both heme-containing enzymes whose activity depends on the cofactor pyridoxal 5Ј-phosphate (6)(7)(8). CBS is capable of catalyzing the reaction of cysteine with other free thiols to generate H 2 S; likewise, thiocysteine generated by CGL can interact with thiols to generate H 2 S (6-8).…”
mentioning
confidence: 99%